Uma contribuição da controladoria para a gestão de um centro de medicina diagnóstica - Silva, Silvio José Moura e (2006)
The changes in the business environment in the last two decades caused huge impact on the healthcare organization s. This new environment encourages the development of a new management process. The decision-making process, which encloses planning, execution and control, becomes important for the companies survival. The management must obtain necessary outcomes to provide companies continuity by handling carefully cost management process, focus on the innovation innovation process and the value creation process for the shareholders. This work intends to use Controllership concepts, limited by cost management area through the use of Activity Based Costing and value creation analysis. The applicability through a Case Study in a Diagnostic Medicine Center is verified in this work. In addition, it intends to present an overview of Diagnostic Medicine area and the Controllership concepts focused on planning, control and aggregate value analysis. An application of Activity Based Costing, EVA® and MVA® is observed considering the organizational intangible assets too. The Controllership must be important part of the management process and the contribution is demonstrated in this work